Physical Activity is Associated with Metabolic Health in Men Living with HIV. - Gormley, John; Forde, Cuisle (My University, 2018)
Metabolic health is a cause for concern among those living with HIV, especially those on antiretroviral therapy. Physical activity (PA) is known to benefit metabolic health, however, few studies have objectively measured PA or investigated the relationship between PA and metabolic health among those living with HIV. In this study, PA and indices of metabolic health among twenty men living with HIV and twenty age matched HIV-negative men were measured. PA was measured using Actigraph accelerometers. Components of the metabolic syndrome and insulin resistance were measured using routine laboratory methods. Men living with HIV were significantly more physically active than HIV-negative men, and were reaching public PA guidelines. Significant inverse correlations between moderate PA and both insulin resistance (ρ -0.847; p < 0.001) and triglycerides (ρ -0.575; p = 0.013) were seen in those living with HIV. Results of this study emphasize the importance of an active lifestyle for those living with HIV.
PUBLISHED
Keywords: HIV; Metabolic syndrome; Physical activity; Sedentary behavior